Fish movement strategies in an ephemeral river in the Simpson Desert, Australia. (11th July 2013) - Kerezsy, Adam; Balcombe, Stephen R.; Tischler, Max; Arthington, Angela H.
Abstract Arid zone catchments experience extreme hydrological variability and some rivers are entirely ephemeral, replenished only by intermittent flooding. The ecological roles of ephemeral systems are rarely studied. This paper describes movement patterns of fish in the Mulligan River, an ephemeral system in the Lake Eyre Basin, central Australia. Several sites were sampled along a temporal gradient encompassing floods and dry periods. After a single major flood in 2007 up to seven fish species were found at sites up to 300 km from the closest permanent waterhole. Following a series of floods (when waterholes were replenished and remained wet between 2009 and 2011) a further five species were recorded including the first records for the Lake Eyre hardyhead, Craterocephalus eyresii, from the rivers of far western Queensland. The presence of all species known from the parent catchment (the Georgina, where permanent waterholes occur) in the ephemeral catchment (the Mulligan) suggests that many fish species present in the river systems of central Australia are capable of dispersing long distances following the opening of movement pathways during flooding. However, two distinct groups of species were identified: extreme dispersing species, that move as far as possible into intermittently wetted habitats, and conservative dispersing species, that do not move as far, tending to inhabit deeper waterholes within mid‐reaches of the river that are more likely to hold water for longer. Preservation of the natural flow regime of Australia's arid‐zone rivers is important for maintaining these fish communities and facilitating study of their adaptations to ephemerality.